2022
DOI: 10.3390/nano12121999
|View full text |Cite
|
Sign up to set email alerts
|

Safety of Lavender Oil-Loaded Niosomes for In Vitro Culture and Biomedical Applications

Abstract: (1) Background: Essential oils have long been used as therapeutic agents. Lavender (Lavandula angustifolia) oil (LO) is an antispasmodic, anticonvulsant, relaxant, painkilling, and antimicrobial essential oil investigated as a natural substance for biomedical therapies. Nanoparticles have shown significant promise in improving drug delivery and efficacy. Considering these benefits, the aim of this study was to evaluate the toxicity of LO and lavender oil niosomes (LONs) in stem cells and myofibroblast models c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…Vilela et al [ 75 ] studied the in vitro safety of lavender oil-loaded niosomes on adipose tissue-derived stem cells (ASCs) and myometrial cells. The cell viability test indicated no significant difference between the viability of untreated cells and those treated with niosomes indicating the biocompatibility of the carrier.…”
Section: Biocompatibility Of Nanovesicles For Dermal and Transdermal ...mentioning
confidence: 99%
“…Vilela et al [ 75 ] studied the in vitro safety of lavender oil-loaded niosomes on adipose tissue-derived stem cells (ASCs) and myometrial cells. The cell viability test indicated no significant difference between the viability of untreated cells and those treated with niosomes indicating the biocompatibility of the carrier.…”
Section: Biocompatibility Of Nanovesicles For Dermal and Transdermal ...mentioning
confidence: 99%
“…Niosomes have been used as delivery systems for a wide range of natural extracts, including flavonoids [ 137 ], terpenoids [ 138 ], alkaloids [ 139 ], and polyphenols [ 140 ], demonstrating that niosomes can improve the solubility, stability, and bioavailability of these natural extracts, thereby enhancing their therapeutic efficacy.…”
Section: Lipid-based Nano-systemsmentioning
confidence: 99%
“…The observation of morphology changes associated with apoptosis after treatment with AuNPs in HT-29 cells suggested the potential use of AuNPs as a pro-apoptotic drug in the treatment of colon cancer [45]. Vilela et al [46] reported that there was no statistically significant difference seen in the vitality of adipose tissue-derived stem cells (ASCs) and myometrial cells after treatment with lavender oil (LO). Moreover, the application of lavender oil and its derivative, niosomal lavender oil (LON), demonstrated cell viability comparable to that of the control culture, indicating their safety for use in cell culture.…”
Section: Antibacterial and Antibiofilm Activity Of The Synthesized Na...mentioning
confidence: 99%